Factors associated with family caregiver readiness to care for post-stroke patients after hospital discharge - Yurike Septianingrum; Ah Yusuf; Ika Yuni Widyawati; Ratna Yunita Sari; Erika Martining Wardani; Naadiyah Roebbi Musfirah; Eni Puji Lestari (Springer, 2024)
Abstract Background Post-stroke patients often need support from their family caregivers to continue their care after hospital discharge. Family caregiver readiness in caring for stroke patients is needed to improve the patient's quality of life. This study aimed to analyze factors affecting family caregivers' readiness for post-stroke patient care after hospital discharge. Methods A cross-sectional study of family members of stroke patients admitted to the neurology inpatient unit from February to April 2023, and they were selected through purposive sampling. The general demographic questionnaire, the stroke knowledge questionnaire, and the Family Readiness for Hospital Discharge Scale (FAM-RHDS) were used to gather the data. Data analysis was performed with IBM SPSS 26 software. Data were examined through the descriptive, Pearson correlation, and multiple linear regression tests. Results Fifty-nine respondents completed the questionnaires. Factors that were significantly related to family readiness to care for stroke patients were age (p = 0.000), gender (p = 0.000), income (p = 0.000), occupation (p = 0.000), marital status (p = 0.000), and knowledge (p = 0.000). Education level was the one that didn't correlate with family readiness (p = 0.452). Gender is the most dominant factor affecting the readiness of family caregivers to care for stroke patients (coefficient B = 10.847). Conclusion Male family caregivers should be given special attention to improve their readiness to care for post-stroke patients. Assessment of family caregivers' readiness for discharge should be part of discharge planning and those who are unprepared may be provided with additional interventions prior to discharge.